Unveiling Liberty (Hinckley Journal of Politics; Vol 7 (2006), 2017)
This article addresses the long-standing debate between Western and Eastern feminists regarding Islamic veiling practices. This debate is, at its core, concerned with the possibility that veiling practices infringe on the liberty of Muslim women, an assertion made by Western feminists and vehemently denied by Eastern feminists. The author argues for a â€œCentristâ€ perspective regarding this issue. Centrism seeks to strike a balance between the extremes of the Eastern and Western perspectives, taking what is most valuable from each and creating a more complete theoretical framework from which to view the issue. By implementing the Centrist strategy, the author asserts, the first steps can be taken toward a cross-cultural feminist account of freedom, one that not only addresses veiling, but endless issues within various cultural societies.